Pengaruh Media Leaflet dan Promosi Kesehatan terhadap Upaya Pencegahan dan Pengendalian Tuberkulosis (TBC) - Sari, Chinta Yolanda; Parisma, Wan Intan; Irawati, Ice (ASOSIASI IDEBAHASA KEPRI, 2024)
Preventive and control measures for tuberculosis (TB) in Indonesia, aiming for TB elimination by 2030, are part of Indonesia's commitment, including sustainable development goals. Limited knowledge, poor behavior, and suboptimal TB prevention and control measures in that company have been observed. The method of activity to be implemented with the community service partner, PT. Lancang Kuning Sukses (LKS), includes: 1) the distribution of leaflets and health promotion to improve workers' knowledge and behavior change in TB prevention and control through questionnaires; 2) direct education and training with company leaders through face-to-face interviews. Based on the results of the community service activities conducted, findings include: 1) a significant improvement in workers' knowledge and behavior towards TB prevention and control through leaflets and health promotion, 2) an awareness from the company to change actions for TB prevention and control in the workplace through direct education and training with company leaders. Based on the community service results, it is concluded that the partner PT. LKS is effective in actions for TB prevention and control at the workplace, thereby helping to reduce TB cases and assisting in the move towards elimination in Indonesia by the year 2030.